Perception and translation of numbers: the case of a health campaign in Denmark. Issue 4 (8th August 2018) - Kristensen, Dorthe Brogård; Jacobsen, Charlotte Bredahl; Pihl-Thingvad, Signe
Abstract: This article explores the translation of numeric health communications from the authorities to ordinary citizens. Based on qualitative interviews and document analysis, it follows the life of a Danish health campaign called '6 a day' from its initiation to its dissemination, and finally to its place in the perceptions and health practices of citizens. While the definition of the target of '6 a day' was clearly anchored in social and scientific contexts, it incorporated considerable ambiguity and scientific uncertainty, flaws which were deliberately kept from citizens. The number '6' was meant to appear unquestionable. We suggest that this way of making and disseminating numeric health campaigns may best be understood as a process of creating a mould and offering it to citizens to fill with their own health practices. Such a process is rife with translations and the article analyses both these and their impact on citizens' health practices and perceptions. We conclude that the success of the campaign lies in its implicit logic and the agency it fosters, rather than its ability to improve health literacy or make citizens aspire to specific health targets. The article thereby contributes to an understanding of the effects of numeric health communications. Health communicators may also gain from an increased awareness of the processes of translation involved in health messages created as moulds.